Lessons Learned by Yugoslav Military Experts from the Soviet Invasion of Afghanistan 1979-1981 - A. Y. Timofeev (Vestnik MGIMO-Universiteta, 2023)
The article analyzes the attitude of Yugoslav military analysts to the deployment of the Soviet troops in Afghanistan in 1979–1981. Afghanistan was not among diplomatic, or military priorities for Yugoslavia. After the coup in Afghanistan on April 27, 1978, relations between the two countries, previously rather formal, deteriorated, as Kabul started to move away from the non-alignment movement taking a pro-Soviet orientation. Yugoslavia saw Afghanistan as a non-aligned country and was extremely concerned about the Soviet interference in the internal affairs of a sovereign state. This political assessment heavily influenced the views of Yugoslav military expert, resulting into some distorted conclusions and numerous overlooked lessons. This testifies to the primacy of everyday political (and even propaganda) needs over military science in Yugoslavia. They believed that Afghanistan would turn into a permanent problem for the USSR. Despite the rich empirical material, Yugoslav analysts did not see any novelty in tactics and the use of new weapons in mountainous areas. They neglected to analyze the tactics of anti-partisan actions in the highlands; their predictions were not original; they ignored the presence of militant fundamentalism as a factor in the conduct of hostilities.